Kemitraan terhadap Risiko Produksi dan Pendapatan Usahatani Kopi Robusta di Provinsi Lampung - Moh. Hasan Basri; Anna Fariyanti; Suharno Suharno (Jurnal Penelitian Pertanian Terapan, 2024)
Lampung Province, as one of the largest producers of robusta coffee in Indonesia, still faces issues of low productivity. Contract farming is seen as a strategy to increase productivity and income from coffee farming. The aim of this research is to analyze the effect of contract farming on production risks and income from coffee farming. The research was conducted in Tanggamus Regency, Lampung Province. The data used in this study is secondary data obtained from the Project Cooperation Agreement (PCA). The research respondents consisted of 203 farmers, comprising 99 partner farmers and 104 non-partner farmers. Data analysis methods used the coefficient of variation to analyze the level of production risk with contract farming and the Mann-Whitney test to analyze income differences between contract and non-contract farmers. The research results showed that both contract and non-contract coffee farmers faced low production risks. Income from coffee farming by adopting a contract farming system was higher than without a contract. Additionally, the total costs incurred for coffee farming by contract farmers were lower than non-contract farmers. Income difference tests between contract and non-contract farmers indicated significant differences in both cash and non-cash income. It can be concluded that farmers under contract and non-contract farmers face the same level of risk, but contract farmers have higher incomes than non-contract farmers.